2011
DOI: 10.1002/cmdc.201100471
|View full text |Cite
|
Sign up to set email alerts
|

Galloflavin (CAS 568‐80‐9): A Novel Inhibitor of Lactate Dehydrogenase

Abstract: One of the most prominent alterations in cancer cells is their strict dependence on the glycolytic pathway for ATP generation. This observation led to the evaluation of glycolysis inhibitors as potential anticancer agents. The inhibition of lactate dehydrogenase (LDH) is a promising way to inhibit tumor cell glucose metabolism without affecting the energetic balance of normal tissues. However, the success of this approach depends chiefly on the availability of inhibitors that display good selectivity. We ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
111
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 164 publications
(116 citation statements)
references
References 39 publications
5
111
0
Order By: Relevance
“…Our results showing that suppressing LDH-A affects cancer cell SIRT1 activity are consistent with a recent study which reports that galloflavin, a novel inhibitor of both LDH isoforms (A and B), 36 reduces SIRT1 activity in Burkitt lymphoma cells. 37 …”
Section: Resultssupporting
confidence: 93%
“…Our results showing that suppressing LDH-A affects cancer cell SIRT1 activity are consistent with a recent study which reports that galloflavin, a novel inhibitor of both LDH isoforms (A and B), 36 reduces SIRT1 activity in Burkitt lymphoma cells. 37 …”
Section: Resultssupporting
confidence: 93%
“…The result is in line with previous reports that showed LDH is a marker of response to NACT for breast cancer patients and oral cancer patients 23, 39. In vitro studies observed LDH is involved in resistance to chemotherapy, which may be an interpretation for the difference in CR rates by LDH levels 40, 41.…”
Section: Discussionsupporting
confidence: 92%
“…In the field of cancer metabolic inhibitors, LDH is considered one of the most promising therapeutic targets; its inhibition as an approach to anticancer was proposed several years ago [65,66] and is currently under active investigation [67][68][69][70][71]. Interest in LDH as an anticancer therapeutic target comes from the observation that this enzyme (namely its -A isoform) becomes constantly up regulated during neoplastic change [49][50][51]54], offering the possibility of a therapeutic intervention aimed at correcting this altered activity.…”
Section: Cancer Cell Metabolism and Ldh: Is There A Basis For A Therapementioning
confidence: 99%
“…By using structure-based virtual screening, a research team from the University of Bologna identified galloflavin (GF) (FiguRe 5B), a gallic acid derivative that inhibits both the A and B LDH isoforms [67]. The adopted virtual screening protocol was based on the crystal structure of the human M subunit of LDH, obtained from the Protein Data Bank [106].…”
Section: Structure-based Virtual Screeningmentioning
confidence: 99%